2019
DOI: 10.1093/carcin/bgz066
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of human malignant mesothelioma tumours and cell lines

Abstract: Pleural mesothelioma is a cancer of serosal surfaces caused by environmental exposure to asbestos. Clinical outcome remains poor and while trials of new treatments are ongoing it remains an understudied cancer. Mesothelioma cell lines can readily be grown from primary tumour and from tumour cells shed into pleural effusion with the latter representing a particularly valuable source of DNA in clinical settings, procurable without the need for additional invasive procedures. However, it is not well understood ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Yoshikawa et al discovered that chromothripsis (ie, chromosome shattering followed by random chromosomal rearrangement) (Fig. A) causes some of the genetic alterations in mesothelioma, a finding independently confirmed by Mansfield et al and most recently by Oey et al Moreover, Mansfield et al predicted that the vast array of genetic alterations in mesothelioma may lead to the production of neoantigens, which correlated with the clonal expansion of tumor‐infiltrating T lymphocytes (Fig. B and 5C) .…”
Section: Carcinogenic Mechanismsmentioning
confidence: 86%
See 1 more Smart Citation
“…Yoshikawa et al discovered that chromothripsis (ie, chromosome shattering followed by random chromosomal rearrangement) (Fig. A) causes some of the genetic alterations in mesothelioma, a finding independently confirmed by Mansfield et al and most recently by Oey et al Moreover, Mansfield et al predicted that the vast array of genetic alterations in mesothelioma may lead to the production of neoantigens, which correlated with the clonal expansion of tumor‐infiltrating T lymphocytes (Fig. B and 5C) .…”
Section: Carcinogenic Mechanismsmentioning
confidence: 86%
“…Because of the carcinogenic “field effect” caused by asbestos, mesotheliomas are often polyclonal . Recently, The Cancer Genome Atlas program published a study of 74 mesotheliomas that were investigated for genetic alterations using next‐generation sequencing (NGS), including whole‐exome sequencing (WES), messenger RNA expression, methylation analysis, microRNA expression, exomes, reverse‐phase protein array, and transcription factor analyses .…”
Section: Carcinogenic Mechanismsmentioning
confidence: 99%
“…Recent studies have addressed this topic in malignant mesothelioma. With the intent to provide reliable cell line models of mesothelioma, Oey et al have characterized the genome of tumors and tumor-derived cell lines through whole genome sequencing (151). Here, the authors have identified recurrent events of high chromosomal instability like chromoanagenesis and chromotripsis.…”
Section: Extensive Chromosomal Breakage: a New Identified Feature In Mesotheliomamentioning
confidence: 99%
“…Intra-tumor heterogeneity is still partially described in MPM, in part due to the use of omics approaches only in bulk tumor samples. MPM is likely a polyclonal tumor that comprises multiple subclones with variable cellular prevalence (41,42). To better define the polyclonal tumor origin and understand the tumor evolution of mesothelioma, further studies are required in a larger number of tumor samples.…”
Section: Mesothelioma Heterogeneitymentioning
confidence: 99%
“…These models remain interesting for screening and preliminary investigations. Primary tumor cells represent an intriguing alternative because they share similar molecular characteristic with the primary tumor, even though they show a reduction of subclonal diversity (15,42,67). However, the necessity to perform studies before 6-10 passages limits the number of experiments.…”
Section: Preclinical Modelsmentioning
confidence: 99%